Kids Today: They Care, But They Don't Think We Do. Issue 4 (2nd October 2022) - Mazzei, Julie; Barnes, Andrew; Roy, Oindrila; Poluse, George
Abstract: Scholars and practitioners know that students flourish when they choose majors that are congruent with their self-conceptions. What is less investigated is the information they have for making that choice and how they gather that knowledge. This study demonstrates that a significant gap exists between student impressions of political science and its associated opportunities, on one hand, and reality, on the other. Specifically, we show that many students substitute their understanding of politics-as-career for an understanding of political-science-as-major, which prevents them from seeing the range of career options opened by the degree. The article also shows that university advisors are an important potential source of student information about major choice, as most universities intend, but they may be unfamiliar with the subject matter and careers associated with particular majors. Finally, we show that intentional efforts to inform advisors, students, and parents of the content and opportunities of a Political Science degree can help close the information gap, and we indicate how the practical strategy described here could be repeated in other settings.